2014
DOI: 10.1016/j.apnr.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethics and work-related factors on nurse practitioners' and physician assistants' views on quality of primary healthcare in the United States

Abstract: Purpose Nurse practitioners (NPs) and physician assistants (PAs) provide primary care services for many American patients. Ethical knowledge is foundational to resolving challenging practice issues, yet little is known about the importance of ethics and work-related factors in the delivery of quality care. The aim of this study was to quantitatively assess whether the quality of the care that practitioners deliver is influenced by ethics and work-related factors. Methods This paper is a secondary data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…The low score in the Physicians dimension might also indicate that there is a lack of support and cooperation between doctors and nurses regarding patient care and one that threatens nurses’ autonomy. 30 In a study of 463 registered nurses, Hart 31 reported the ethical climate in acute care hospitals to be the most important variable predicting turnover intention, staffing, workload, and feelings of autonomy. The lack of trust, respect, and support creates a negative climate in the care sector and is a source of stress and dissatisfaction among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The low score in the Physicians dimension might also indicate that there is a lack of support and cooperation between doctors and nurses regarding patient care and one that threatens nurses’ autonomy. 30 In a study of 463 registered nurses, Hart 31 reported the ethical climate in acute care hospitals to be the most important variable predicting turnover intention, staffing, workload, and feelings of autonomy. The lack of trust, respect, and support creates a negative climate in the care sector and is a source of stress and dissatisfaction among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, national (27)(28) and international (19,(29)(30) studies reveal the continuous and epistemological teaching of Ethics and Bioethics as the best way to answer, deliberate and analyze deeply, critically and argumentatively the ethical and bioethical problems, considering, above all, the moral conduct and the ethical-professional obligations.…”
Section: Discussionmentioning
confidence: 99%
“…There is an established positive correlation between professional autonomy and higher education on attitude towards caring for dying patients [ 29 ] which presupposes that higher carrier development and years of experience are most likely to positively influence professional ethical standards in nursing care including ethical decision making for postoperative pain management. Studies also revealed that nurse practitioners who had knowledge of professional ethics such as autonomy were confident in healthcare delivery decisions which improved their quality of work [ 30 ]. This presupposes that as professional nurses know ethics relating to pain management, they will give satisfactory care.…”
Section: Introductionmentioning
confidence: 99%